Mathematics Learning Experience at the Basic School and Its Influence on One’s Program of Choice at the Institution Higher of Learning - Amoako Atta, Seth; Jeneva Clark, Lauren; Bonyah, Ebenezer (Manunggal Halim Jaya, 2023)
This paper sought to determine if the Basic School Mathematics learning experience has any influence on the individual when it comes to program selection in higher education and career choice. The researcher employed a qualitative approach in order to obtain detailed information about the topic. This led to the adoption of the Narrative Paradigm, where one experienced person was interviewed to obtain first-hand information for analysis. It was revealed if a student develops an interest in mathematics at Basic School it improves their performance. More so such a student is more likely to enroll in mathematics-related courses as he or she moves higher on the academic ladder. It was also observed that if teachers adopt methods of teaching that are learner-centered, it motivates the learner to learn mathematics as an integral part of life but not as abstract information that needs to be chewed. The study confirmed that mathematics has various applications in the workplace, and knowledge of mathematics can be self-gratifying. The study makes the following recommendations; even though students learn as a group, the teacher must focus on the individual learners by giving them extra attention, teachers must be interested in what the students learn after school, and teachers must keep parents and guardians informed about the academic achievements progress of their wards.